A review of aircraft wing mass estimation methods - Dababneh, Odeh; Kipouros, Timoleon (Elsevier, 2017)
In this paper, the current state of the art of aircraft wing mass estimation methods is reviewed. The phases of aircraft design and the development process are discussed. The open literature on the subject of wing mass estimation methods and their applications in the aerospace industry is discussed, and relevant data are presented to provide the reader with background information on the field. Special attention is given to classifications of wing mass estimation methods. Current challenges and technological difficulties in wing mass estimation methods are identified, and perspectives are drawn and used to propose several key ideas for future research in the field.
Keywords: Wing mass estimation; Aircraft design process; Empirical methods